answersLogoWhite

0


Best Answer

x2 - 6x = 16

∴ x2 - 6x + 9 = 25

∴ (x - 3)2 = 25

∴ x - 3 = 25

∴ x = 28

User Avatar

Wiki User

βˆ™ 2010-01-17 17:34:25
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

➑️
See all cards
3.75
β˜†β˜…β˜†β˜…β˜†β˜…β˜†β˜…β˜†β˜…
1048 Reviews

Add your answer:

Earn +20 pts
Q: How do you complete the square x2 - 6x equals 16?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

The square root of 6x-2 equals 4?

root (6x - 2) = 4 therefore 6x - 2 = 16 therefore 6x = 16 + 2 therefore x = 3


What is the answer to the equation -10 equals 6x - 16?

-10 = 6x - 16, or 16 - 10 = 6x, or x = 1.


The square root of 6x-2 equals 4 what is the solution set?

If the square root of 6x-2=4 than we can square both sides and we have 6x-2=16 or 6x=18 and the solution set is the set that contains the number 3.


Y equals 6x-16 y equals -2x plus 8?

y=6x-16 y=-2x+8


What is the answer of 8x plus 16 equals 6x?

8x + 16 = 6x -> 2x + 16 = 0 -> 2x = -16 -> x = -8


How do you solve for -16 equals 6x?

-16 = 6x Swap: 6x = -16 Divide both sides by 6: x = -16/6 = -8/3 or -22/3 or -2.66...


What are the solutions in completing the square x2 plus 6x equals 7?

x2 + 6x = 7 ⇒ x2 + 6x + 9 = 7 + 9 ⇒ (x + 3)2 = 16 ⇒ x + 3 = ±4 ⇒ x = -7 or 1


Is the solution of -6x equals -16 greater than or less than -16?

The solution of -6x = -16 is x = 2 2/3, which is greater than -16.


What is the Equation for x 6x - 14x plus 16 equals -27 plus 11?

6x-14x+16=27+11 answer: 4


How do you solve the square root of 6x minus 3 minus the 3 times the square root of x equals 1?

√(6x) - 3 - 3√x = 1 √(6x) -3√x = 4 √x = 4/(√6 - 3) = -4(√6 + 3)/3 = 16/9*(15+6√6) = 16/3*(5+2√6) = 52.8, approx.


If 6x - 2 equals 16 what is the value of x - 3?

6x - 2 = 16 : 6x = 16 + 2 = 18 : x = 18÷ 6 = 3 :x - 3 = 3 - 3 = 0 : x - 3 = 0


How do you solve 9 plus 6x equals 25-2x?

9+6x = 25-2x 6x+2x = 25-9 8x = 16 x = 2

People also asked